Afterlife with Archie. Book one, Escape from Riverdale - Aguirre-Sacasa, Roberto; Francavilla, Francesco; Morelli, Jack.; Goldwater, John L.; Montana, Bob. (2014)
"All hell breaks loose when a fateful accident sets in motion a series of terrifying events that will threaten the town of Riverdale like never before! When the dead begin to rise, craving human flesh, it's up to Archie, Betty & Veronica, and the Gang to fight for their lives against the zombie hordes led by their former pal, Jughead."--Back cover.
"Archie characters created by John L. Goldwater; the likenesses of the original Archie characters were created by Bob Montana."
Keywords: Zombies -- Comic books, strips, etc; Graphic novels; Comic books, strips, etc